THE POWER OF ONLINE MEDIA: CRITICAL DISCOURSE ANALYSIS OF SECURITY CRITICS (Proceeding of the International Conference on Arts and Humanities, 2018)
Security issue has become the most reported headline in mass media. This issue is categorized as hard news, which is covered and reported as soon as it happens. All aspects which are written and displayed in the text could influence the readers. Although many believe that news exist to inform the reader, news can be misled and contain specific point of view toward some issues. Critical discourse analysis becomes the tool to find out how editor use their power in composing text. This research is using qualitative method to a text from online media talking about security critics. As for verbal aspect, researcher is using appraisal theory (Martin and White, 2005) and for nonverbal aspect is using news value of photography by Caple (2013). The result is the differences in distribution in negativity aspects as the verbal one carries more negative aspects than the nonverbal. The result also shows how the writer and editor’s position and tendency toward the event in reporting news such as negative judgment.
Keywords: critical discourse analysis; multimodality; appraisal; visual value